Depressive symptoms and associated social and environmental factors among women living in informal settlements in Nairobi, Kenya. Issue 1 (2nd January 2023) - Winter, Samantha; Musyimi, Christine; Mutiso, Victoria; Ndetei, David
ABSTRACT: Approximately 280 million people around the world suffer from depression, and the rates are higher among women than men. For women living in informal settlements in lower – and middle-income countries (LMICs) the prevalence and associated burden of depressive symptoms may be particularly high. The purpose of this paper was to explore factors associated with possible major depressive disorder (MDD) in a probability sample of women living in Mathare informal settlement in Nairobi, Kenya and to identify potential points for intervention and/or support. Quantitative surveys were conducted with 552 women aged 18–75. Possible MDD was measured using the Patient Health Questionnaire and regressed on individual, household/familial-, and community/interpersonal-level factors. Findings highlight the potential importance of factors such as physical health, economic stress, access to water and sanitation, household and family dynamics, and neighbourhood/village differences in possible MDD among women living in informal settlements. We identify potential points for research, intervention and policy including: providing appropriate tangible assistance or interventions to reduce economic stress/strain; expanding access to water and sanitation and, in doing so, reducing potential burdens to physical health; providing and expanding healthcare to include mental healthcare; and investigating family dynamics and bolstering support for families, particularly for those experiencing conflict.